Raising of Lazarus: Rediscovery and redescription of Apostolepis niceforoi Amaral, 1935 (Serpentes: Dipsadidae: Elapomorphini) - Entiauspe-Neto, Omar M.; Medina Rangel, Guido Fabian; Guedes, Thais B.; Tiutenko, Arthur (Holotipus rivista di zoologia sistematica e tassonomia, 2020)
Apostolepis is a speciose Neotropical snake genus, encompassing 38 species, widely distributed in South America. Most species of the genus are known based on small series, which has contributed to a convoluted taxonomic history. In this study, we report the rediscovery of Apostolepis niceforoi, a taxon that remained knownfrom a single specimen since its original description in 1935, providing a detailed redescription, with c
Keywords: Caenophidia; Colombia; Neotropical; Taxonomy